2012
DOI: 10.3109/10428194.2012.696313
|View full text |Cite
|
Sign up to set email alerts
|

Chronic myeloid leukemia stem cells display alterations in expression of genes involved in oxidative phosphorylation

Abstract: Mitochondrial respiratory chain (MRC) consists of the protein complexes I, II, III, IV, and V to carry oxidative phosphorylation (OXPHOS), which depends on electron transport to generate ATP. Electron "leakage" from MRC generates reactive oxygen species (ROS). Chronic myeloid leukemia in chronic phase (CML-CP) stem cells (LSCs) produce high levels of mitochondrial ROS causing oxidative DNA damage resulting in genomic instability generating imatinibresistant BCR-ABL1 kinase mutants and additional chromosomal ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 19 publications
3
24
0
Order By: Relevance
“…In embryonic, neural, normal, and tumoral breast tissues, stem/progenitor cells contain lower level of reactive oxygen species than their more mature progeny, sustaining their relative resistance to radiation (40,41). In leukemia, oxidative phosphorylation triggers genomic instability and is a putative mechanism explaining relapse after tyrosine kinase inhibitor treatment (42,43). Noteworthy, aldehyde dehydrogenase, a hallmark of embryonic, normal adult tissue and CSCs, oxidizes aldehydes to the corresponding carboxylic acids (44).…”
Section: /Cd24mentioning
confidence: 99%
“…In embryonic, neural, normal, and tumoral breast tissues, stem/progenitor cells contain lower level of reactive oxygen species than their more mature progeny, sustaining their relative resistance to radiation (40,41). In leukemia, oxidative phosphorylation triggers genomic instability and is a putative mechanism explaining relapse after tyrosine kinase inhibitor treatment (42,43). Noteworthy, aldehyde dehydrogenase, a hallmark of embryonic, normal adult tissue and CSCs, oxidizes aldehydes to the corresponding carboxylic acids (44).…”
Section: /Cd24mentioning
confidence: 99%
“…The greater prevalence of genetic instability in leukemic cells of patients with advanced disease arises from enhanced DNA damage and reduced capacity to repair that damage. Both BCR-ABL–dependent [16,17] and –independent [18] mechanisms of generating reactive oxygen species can contribute to overall genomic instability by inducing oxidative DNA damage such as double-strand breaks [19]. Furthermore, in vitro experiments have demonstrated that expression of BCR-ABL protein sensitizes cells to ionizing radiation [20] and causes cells to accumulate drug-induced DNA damage [21].…”
Section: Potential Mechanisms Of Disease Progression In CMLmentioning
confidence: 99%
“…Point mutations, double strand breaks and translocations arising from oxidative stress are commonplace with elevated reactive oxygen species (ROS) generated by mitochondrial respiration mediating such DNA damage [1, 2]. Genetic lesions are of particular significance in stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…The ‘reactive oxygen driven' solid tumor has previously been described, characterized by high levels of superoxide generation in tumor cells [13] that are often refractory to conventional chemotherapy, targeted therapy and radiation [2, 14]. Previously we have demonstrated the efficacy of the synthetic NADPH oxidase inhibitor imipramine blue (IB) to block the invasion of glioblastoma multiforme (GBM) into the brain parenchyma [15], and therefore, prolong survival in animal models likely through eradication of ROS-driven GBM stem cells.…”
Section: Introductionmentioning
confidence: 99%